Biometric relationships of the Fat sleeper Dormitator maculatus (Blotch, 1792) (Teleostei: Eleotridae) from Alvarado lagoon, Veracruz, Mexico - Franco-López, Jonathan; Abarca-Arenas, Luis Gerardo; Peláez-Rodríguez, Edgar; Viveros-Legorreta, José Luis; González-Acosta, Adrian Felipe (Ecosistemas y Recursos Agropecuarios, 2021)
L-W and eight biometric relationships for D. maculatus in the Alvarado lagoon, were performed on 500 specimens (252 females and 248 males), 23.7 - 143.9 cm TL and 0.95 – 59.1 g weight, sampled during May 2015 to May 2017, using traditional fishing gears. The b coefficient indicated isometric growth (b = 3.0195; r2 >0.9763; P < 0.05) for overall sample, females (b = 3.0507; r2 >0.989; P < 0.05) and males (b = 2.9953; r2 >0.9783 P < 0.05). Biometric relationships showed high correlations (r2 >0.9193 – 0.9992; P < 0.05) for the overall sample. females (r2 >0.9188 – 0.9981; P < 0.05) and males (r2 >0.9079 – 0.9995; P < 0.05). This study report for the first time L-W and biometric relationships for the Fat sleeper. These results will be useful to delineate a baseline for regulations and the sustainable fishery management of this fish species
Keywords: LWR parameters; biometry; growth; regression models; eleotrid fish; Gulf of Mexico